Analysis of changes in water production using a rural water treatment plant as an example - Wawrentowicz, Dariusz (Instal, 2023)
The paper presents the characteristics of water production at a water treatment plant supplying rural areas. The main focus of the study was to determine the coefficients of daily (ND) and hourly (Nh) irregularities in water production that occur in rural areas and to analyse the impact of the use of storage tanks in the process line of the water treatment station on the values of hourly irregularity coefficients. In order to achieve the objectives of the study, the readings of the values of water produced at the station were used and compared with the amount of treated water entering the water supply system from the SCADA system from the water meter installed at the raw water inflow to the water treatment station and at the outflow from the retention tanks. Water outflows were considered over the year 2021. A technological start-up of the water treatment plant took place during the study period, but this did not significantly affect the increase in water outflows on an annual basis. The coefficient of daily unevenness calculated for the study period was 1.50, while the coefficient of hourly unevenness assumed the value of 1.84.